Modelling of flood flushing in a tributary constrained by barrages - Mah, Yau Seng; Putuhena, F.J.; Rosli, N.A (IDOSI Publication, 2011)
Purpose – Flood flushing is one natural cleansing capability of a natural river channel to wash away in‐stream pollutants and debris. The purpose of this paper is to explore the flood flushing restriction in a tributary due to its regulated main river channel between two barrages.